Pushing the boundaries of optoacoustic microscopy by total impulse response characterization - Markus Seeger (Nature Portfolio, 2020)
Characterizing the total impulse response (TIR) of photoacoustic microscopes has been challenging due to difficulties distributing appropriate point sources. Here, the authors present a method for 3D generation of spatially-distributed optoacoustic point sources and show that subsequent TIR correction results in improved image quality.